Molecular Phylogeography Analysis Reveals Population Dynamics and Genetic Divergence of a Widespread Tree Pterocarya stenoptera in China - Qian, Zhi-Hao; Li, Yong; Li, Ming-Wan; He, Yan-Xia; Li, Jia-Xin; Ye, Xiao-Fan (Frontiers in Genetics, 2019)
The geological events, past climatic fluctuations and river systems played key roles in the spatial distribution, population dynamics and genetic differentiation of species. In this work, we selected Pterocarya stenoptera, a widespread tree species in China, to test the roles of these factors. Four noncoding spacers, eight microsatellite (SSR) markers, and species distribution modeling were used to examine the phylogeographical pattern of P. stenoptera. Based on cpDNA data, populations of P. stenoptera were clearly clustered into three groups. The divergence time of these groups fell into the stage of the Qinghai–Tibet Movement, 1.7 to 2.6 Ma. For SSR data, only one western marginal population YNYB could be separated from other populations, whereas other populations were mixed together. Our results indicated that the environmental heterogeneity resulting from the Qinghai–Tibet movement might be response for this genetic divergence. The climatic fluctuations in the Pleistocene did not cause the substantial range shift of P. stenoptera, while the fluctuations affected its population size. Moreover, we also confirmed the river systems did not act as channels or barrier of dispersal for P. stenoptera.